2015
DOI: 10.1002/ejoc.201500815
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of 3‐Oxo‐ and 3β‐Hydroxytauranin via Negishi Coupling of a Bis(ortho‐oxy)‐Functionalized Benzyl Chloride

Abstract: The first asymmetric synthesis of the sesquiterpene quinones 3‐oxo‐ and 3β‐hydroxytauranin (1, 2) was achieved and the originally proposed structure of 3α‐hydroxytauranin was revised. The protected benzyl chloride 5 was obtained in six steps starting from 4‐bromo‐3,5‐dihydroxybenzoic acid (8) via a highly scalable approach. The troublesome Negishi coupling of the benzyl chloride 5 with alkenyldimethylalane 6 was optimized to furnish all‐trans‐farnesylarene 14 in very good yield. This prenylated arene was trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Substantially pure compound 9 (9:9' > 20:1) was obtained via extensive chromatography,a nd was used in subsequent investigations. [10] To synthesize quinone 3,d ifferent oxidants were examined for the oxidation of resorcinol 9,s uch as PbO 2 ,P hI-(OAc) 2 ,P hI(TFA) 2 , [11] MnO 2 ,a nd K 2 NO(SO 3 ) 2 (FrØmys salt). [12] To our surprise,w ef ound that five equiv of FrØmys salt directly oxidized resorcinol 9 to adimeric compound 7' in 14 %y ield in am ixture of THF and pH 8p hosphate buffer (Scheme 2) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Substantially pure compound 9 (9:9' > 20:1) was obtained via extensive chromatography,a nd was used in subsequent investigations. [10] To synthesize quinone 3,d ifferent oxidants were examined for the oxidation of resorcinol 9,s uch as PbO 2 ,P hI-(OAc) 2 ,P hI(TFA) 2 , [11] MnO 2 ,a nd K 2 NO(SO 3 ) 2 (FrØmys salt). [12] To our surprise,w ef ound that five equiv of FrØmys salt directly oxidized resorcinol 9 to adimeric compound 7' in 14 %y ield in am ixture of THF and pH 8p hosphate buffer (Scheme 2) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The 2,6-diisopropylphenyl sulfide moiety was cleanly reduced by lithium naphthalenide, along with the concomitant reductive cleavage of the tosyl protecting group ( Scheme 9 ). 25 The absolute configuration of the reduced product, 2-methylindoline, was compared to literature values and assigned the ( R )-configuration. 26 …”
Section: Resultsmentioning
confidence: 99%
“…To synthesize quinone 3 , different oxidants were examined for the oxidation of resorcinol 9 , such as PbO 2 , PhI(OAc) 2 , PhI(TFA) 2 , MnO 2 , and K 2 NO(SO 3 ) 2 (Frémy's salt) . To our surprise, we found that five equiv of Frémy's salt directly oxidized resorcinol 9 to a dimeric compound 7 ′ in 14 % yield in a mixture of THF and pH 8 phosphate buffer (Scheme ) at room temperature .…”
Section: Figurementioning
confidence: 94%